Mechanical Strain Regulates Myofibroblast Differentiation of Human Scleral Fibroblasts by YAP - Hu, Di; Jiang, Junhong; Ding, Baiyang; Xue, Kang; Sun, Xinghuai; Qian, Shaohong (Frontiers in Physiology, 2021)
Scleral extracellular matrix (ECM) remodeling is thought to play a critical role in the pathogenesis of glaucoma. Mechanical strain induced by elevated intraocular pressure can promote myofibroblast differentiation of fibroblasts and result in scleral ECM remodeling, however; the underlying mechanism remains poorly understood. Yes-associated protein (YAP) is a mechanosensory protein and the key downstream transcriptional effector of the Hippo signaling pathway. Here, we investigated the role of YAP in mechanical strain-induced myofibroblast transformation during glaucoma scleral ECM remodeling. Integrative bioinformatics analyses were performed to identify the key pathways for the ECM remodeling of sclera in glaucoma. Sprague–Dawley rats were used to establish a chronic ocular hypertension model, and the expression of type I collagen (COL1) and YAP in the sclera was analyzed by immunohistochemical analysis and Western blotting. Furthermore, human scleral fibroblasts (HSFs) were cultured and subjected to mechanical strain. In groups with or without the YAP siRNA or YAP inhibitor, cell proliferation, migration capacity, and the expression levels of YAP, COL1 and α-smooth muscle actin (α-SMA) were evaluated by Cell Counting Kit-8 (CCK-8) assay, scratch assay and Western blotting. The interactions between YAP and Smad3 were demonstrated by co-immunoprecipitation, and the expression levels of COL1 and α-SMA were evaluated in groups treated with or without the Smad3 inhibitor. We first revealed that the Hippo signaling pathway may be involved in mechanical strain-induced scleral ECM remodeling through bioinformatics analysis. Furthermore, the in vivo study showed upregulated YAP, COL1 and α-SMA expression in the hypertensive sclera of rats. In vitro, mechanical strain-increased YAP and COL1 expression in HSFs and promoted myofibroblast differentiation. After YAP knockdown or inhibition with verteporfin, mechanical strain induced fibrotic changes in HSFs were markedly suppressed. Additionally, YAP showed a protein interaction with Smad3, and the upregulation of a-SMA and COL1 in response to mechanical strain was also significantly downregulated following the inhibition of Smad3. In conclusion, mechanical strain activated scleral myofibroblast differentiation via YAP. The YAP pathway may play an important role in regulating scleral myofibroblast differentiation and ECM remodeling of the sclera in glaucoma.